HUBUNGAN DUKUNGAN KELUARGA DENGAN PENGAMBILAN KEPUTUSAN TERAPI HEMODIALISA - Apriliana, Dwi; Budi Prabowo, Dwi Yogo; Risca Megawati, Riris (NHM PRESS, 2024)
Chronic Kidney Disease Stage 5 is a progressive and irreversible kidney function disorder. This condition necessitates that patients with chronic kidney failure receive kidney replacement therapy, such as haemodialysis. Haemodialysis is a method of treating patients with chronic kidney failure that requires a lot of money, not just 1-2 months. But it also takes quite a long time. Without family support, it is impossible to carry out haemodialysis treatment according to the scheduled schedule. The main problem faced by patients when they first undergo haemodialysis is decision-making. After receiving a diagnosis of chronic kidney failure, patients often feel uncertain about making decisions about haemodialysis therapy. This study aims to determine the relationship between family support and haemodialysis therapy decision-making. This research is a correlational analytical study with a cross-sectional approach. The number of samples in this study was 103, and data collection techniques used random sampling. Based on the Spearman Rank test, the research results showed that there was a relationship between family support and haemodialysis therapy decision-making (p-value = 0.000, p<0.05). This research suggests that families should provide good family support, including self-esteem support, information, instrumentality, social closeness, and motivation, to aid in haemodialysis therapy decision-making.